Four theoretical issues and a funeral: improving the policy-guiding value of eco-efficiency indicators. (1st September 2004) - Jollands, Nigel; Patterson, Murray
For eco-efficiency indicators to be useful in guiding policy, four issues must be resolved: the meaning of "eco-efficiency", the meaning of "eco-efficiency indicator", the criteria for choosing the most suitable eco-efficiency indicator(s), and the strengths and limitations of eco-efficiency indicators for guiding policy makers' decisions. These issues, if not resolved, may prove to be the death knell of the use of eco-efficiency indicators for policy development. This paper addresses each of these issues in detail. In doing so, we hope to avert the need to make funeral arrangements for a potentially promising policy tool.